1997
DOI: 10.1002/(sici)1097-4679(199702)53:2<123::aid-jclp5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

A two-factor model of dietary restraint

Abstract: The present study was designed to examine the factorial nature of the Three Factor Eating Questionnaire-Restraint Scale (TFEQ-R) and to compare the relationship of both the Restraint Scale (RS) and TFEQ-R to current dieting, history of dieting, disinhibition, self-esteem and restrained drinking in 144 females. A principal component analysis identified three interpretable factors: Emotional/Cognitive Concern for Dieting, Calorie Knowledge, Behavioral Dieting Control. Only Emotional/Cognitive Concern for Dieting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…10,29 Analysis in the present study also indicated more than one measurement dimension, Behavioral Restraint and Food Awareness. These factors were, however, strongly correlated and items could not be included in separate scale constructs according to multitraitamulti-item analysis criteria.…”
Section: Discussionsupporting
confidence: 61%
“…10,29 Analysis in the present study also indicated more than one measurement dimension, Behavioral Restraint and Food Awareness. These factors were, however, strongly correlated and items could not be included in separate scale constructs according to multitraitamulti-item analysis criteria.…”
Section: Discussionsupporting
confidence: 61%
“…33 This strategy takes account of both the sample size and the number of items being analysed. Again, while this strategy diverges from that used by Ricciardelli and Williams, 25 use of the eigenvalues greater than one rule 34 with the current sample produced more factors than could be realistically interpreted. Finally, items attaining a loading of 0.45 or better on any retained factor were examined to determine their suitability for scale construction (ie, internal reliability) using alpha (a).…”
Section: Discussionmentioning
confidence: 60%
“…First, a principle component analysis (PC) was conducted in order to replicate Ricciardelli and Williams. 25 Unfortunately, factor solutions obtained using this procedure either did not converge or did not produce interpretable factors. Therefore, principal axis factoring was conducted to screen for redundant items.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations